2009
DOI: 10.1007/s10725-009-9366-z
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous expression of OsWRKY23 gene enhances pathogen defense and dark-induced leaf senescence in Arabidopsis

Abstract: WRKY proteins are a superfamily of plant transcriptional factors with potential regulatory roles pertaining to a variety of biotic and abiotic stress responses. In this study, we investigated the expression profiles of Os-WRKY23 under different developmental stages, pathogen infection, continuous-dark and hormone treatments. Under normal growth conditions, OsWRKY23 expressed exclusively in roots and senescing leaves. Under biotic and abiotic stresses treatments, OsWRKY23 was markedly induced by continuous-dark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(60 citation statements)
references
References 51 publications
0
59
0
1
Order By: Relevance
“…Although the similarity between AtWRKY22 protein and At-WRKY53, AtWRKY6, OsWRKY23 proteins is not high, the relative high expression level of AtWRKY22 was found to be the same as AtWRKY53 and OsWRKY23 under the condition of dark-induced senescence (Jing et al, 2009;Miao et al, 2004) (Figs. 2D and 7D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the similarity between AtWRKY22 protein and At-WRKY53, AtWRKY6, OsWRKY23 proteins is not high, the relative high expression level of AtWRKY22 was found to be the same as AtWRKY53 and OsWRKY23 under the condition of dark-induced senescence (Jing et al, 2009;Miao et al, 2004) (Figs. 2D and 7D).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous work showed that the expression of Oryza sativa WRKY23 was induced by the dark and that heterologous expression of OsWRKY23 enhanced dark-induced leaf senescence in Arabidopsis (Jing et al, 2009). In addition, certain Arabidopsis WRKY genes have important roles in dark-induced senescence signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported that expression of WRKY genes in plants is induced by abiotic stresses (Rizhsky et al 2002;Ulker and Somssich 2004;Marchive et al 2007;Jing et al 2009). In the present study, VpWRKY1 and VpWRKY2 transgenic Arabidopsis plants are more capable of adapting to the salt stress during germination (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that WRKY transcription factors also play important roles in physiological and developmental programs, including senescence, seed germination and trichome development (Hinderhofer and Zentgraf 2001;Johnson et al 2002;Singh et al 2002). OsWRK23 enhances dark-induced leaf senescence in Arabidopsis (Jing et al 2009), while AtWRKY22 participates in the dark-induced senescence signal-transduction pathway (Zhou et al 2011). AtWRKY2 mediates seed germination and post-germination arrest of development by ABA (Jiang and Yu 2009), and AtWRKY57 functions as a node of convergence for jasmonic acid-and auxin-mediated signaling in jasmonic acid-induced leaf senescence (Jiang et al 2014).…”
Section: Introductionmentioning
confidence: 99%